Do More of Those in Misery Suffer from Poverty, Unemployment or Mental Illness? - Sarah Flèche; Richard Layard (Institute for the Study of Labor (IZA), 2015)
Studies of deprivation usually ignore mental illness. This paper uses household panel data from the USA, Australia, Britain and Germany to broaden the analysis. We ask first how many of those in the lowest levels of life-satisfaction suffer from unemployment, poverty, physical ill health, and mental illness. The largest proportion suffer from mental illness. Multiple regression shows that mental illness is not highly correlated with poverty or unemployment, and that it contributes more to explaining the presence of misery than is explained by either poverty or unemployment. This holds both with and without fixed effects.
Keywords: I1; I31; I32; 330; mental health; life-satisfaction; wellbeing; poverty; unemployment